A pilot study to assess the morphology and progression of non-carious cervical lesions. (February 2017) - Sugita, Iori; Nakashima, Syozi; Ikeda, Asaomi; Burrow, Michael F.; Nikaido, Toru; Kubo, Shisei; Tagami, Junji; Sumi, Yasunori
Abstract: Objective: This longitudinal pilot study aimed to morphologically and quantitatively investigate the progress of non-carious cervical lesions (NCCLs) by using swept-source optical coherence tomography (SS-OCT). Methods: The samples examined comprised sets of NCCL epoxy resin replicas obtained from 10 lesions in 6 patients who attended annual dental visits over 4 or 5 years. SS-OCT images of the replicas were analyzed in terms of the maximum depth (Dmax ) and corresponding vertical width (VW) – using an image analyzer to estimate progression of the NCCLs over time. Results: It was found that differences between wedge- and saucer-shaped lesions were morphologically distinguished well by the OCT images. There were significant differences in dimensions among Dmax, VW and horizontal width (HW). HW was the largest and Dmax was the smallest. Although no significant differences in absolute values of annual progression rates were found among Dmax, VW and HW, the percentage increase in Dmax was significantly greater compared to VW and HW. The ratios of Dmax to corresponding VW ranged from 0.49 to 1.01 for the wedge-shaped lesions and from 0.13 to 0.44 for saucer-shaped lesions, respectively. Conclusions: The dimensional analysis demonstrated notable progression with large variations. The wedge-shaped lesions appeared to show greater Dmax values compared to the saucer-shaped lesions. Clinical significance: With respect to the depth, the wedge-shaped lesions may progress at a greater rate compared to the saucer-shaped lesions.